Significance of Zone 2 Peak on Capillary Electrophoresis in the Detection of Hemoglobin Constant Spring - Marini Ramli; Nik Fatma Fairuz Nik Mohd Hasan; Majdan Ramli; Wan Suriana Wan Ab Rahman; Mohd Nazri Hassan; Noor Haslina Mohd Noor; Shafini Mohamed Yusoff; Salfarina Iberahim; Rosnah Bahar; Zefarina Zulkafli (Oman Medical Journal, 2023)
Objectives: Hemoglobin constant spring (Hb CS) is a point mutational defect associated with α thalassemia. The aims of this study were to compare the hematological profiles between different Hb CS genotypes and to estimate the range for Zone 2 peak using capillary electrophoresis (CE) with different Hb CS genotypes. Methods: For this cross-sectional study, patient blood samples that showed a positive peak in zone 2 of CE were selected. Hemoglobin and DNA of the samples were investigated to ascertain the presence and levels of non-deletional and deletional α thalassemia. The results were statistically analyzed. Results: Of the 137 samples investigated, 118 (86.1%) were positive for termination codon Hb CS mutation. Heterozygous Hb CS was found in 92 (67.2%), compound heterozygous Hb CS in 22 (16.1%), and homozygous Hb CS in four (2.9%) samples. The ranges of Hb CS level for heterozygous Hb CS, compound heterozygous Hb CS, and homozygous Hb CS were within 0.2–2.7%, 0.3–2.2%, and 4.5–5.5%, respectively. Significant hematological differences in the Hb level, mean cell volume, mean cell hemoglobin, red cell distribution width, red blood cell count, and Hb CS level were observed between heterozygous, homozygous, and compound heterozygous Hb CS. Conclusions: In view of the overlapping prevalence range of Hb CS level for heterozygous and compound heterozygous Hb CS, only Hb CS level within the range 4.5–5.5% was helpful in the diagnosis of homozygous Hb CS.